Study Of Hydrometeorological Disaster Awareness In Community Of Langsa City - Afrian, Ramdan; Suciani, Ayu; Islami, Zukya Rona; Marfai, Muh. Aris; Hizbaron, Dyah Rahmawati; Urfan, Faiz (Universitas Pendidikan Indonesia, 2021)
The phenomenon of hydrometeorological disasters almost every year occurs in Langsa City. The disaster in losses for the community and the Langsa city government. To reduce the impact of the disaster, it was necessary to prepare the community in synergy with the government. Langsa Lama and Langsa and East Langsa sub-districts are the areas most frequently affected by hydrometeorological disasters, this is in accordance with data obtained from the Langsa City BPBD. The purpose of this study is to determine the awareness and level of sensitivity of the community to the disaster that will be faced, which can later be taken into consideration by the Langsa City government in reducing disaster risk. This research method is descriptive (survey), data obtained from observation and documentation questionnaires. Data processing techniques are carried out using the Gultman scale. The results of the study indicate that there is a need for a change in the education system. Disaster education is carried out by generalizing education intended to increase awareness training for emerging disasters. To achieve success in disaster training, it is important for the central government, local governments and civil society organizations to work in a coordinated manner. Exercises should be carried out periodically in family and community education, volunteer civilian disaster medical assistance teams should be formed in each ward and pro-disaster collection area transferred to families Disaster education is carried out by generalizing education intended to increase awareness training for emerging disasters. To achieve success in disaster training, it is important for the central government, local governments and civil society organizations to work in a coordinated manner. Exercises should be carried out periodically in family and community education, volunteer civilian disaster medical assistance teams should be formed in each ward and pro-disaster collection area transferred to families Disaster education is carried out by generalizing education intended to increase awareness training for emerging disasters. To achieve success in disaster training, it is important for the central government, local governments and civil society organizations to work in a coordinated manner. Exercises should be carried out periodically in family and community education, volunteer civilian disaster medical assistance teams should be formed in each ward and pro-disaster collection area transferred to families